Stabbing to get to prison: biography as an encounter with the criminal mind - Gemert, Frank van (Criminological encounters, 2018)
Stabbing someone because of a minor altercation and then turning yourself in, knowing that you will be convicted of a serious crime, doesn't seem to make sense. One needs to know the perpetrator and the life he lived in order to understand the why and how of this offence. Doing research for writing an authorized biography enables such deep immersion, because of the quality of data gathered on the single person. While it is common in criminology, as well as for writing a biography, to use an approach with a focus on structure and stress context and background factors, in this study an interaction perspective is added to include what happens in the foreground. "An encounter with the criminal mind" can be understood as a personal meeting with a protagonist who commits crimes, but it can also refer to a close look at the criminal act and bring to the surface what the protagonist was thinking and feeling at that time.